The Field Measurement and Experimental Verification of Subway Platform Piston Wind Attached Jet Theory - Wang Lihui; Du Xiaoming; Ren Jun; Han Xing; Gong Wei; Song Jie; Jiang Xing (Zhileng xuebao)
To study the platform piston wind distribution characteristics from the mechanism, it is put forward that the characteristics of platform piston wind conform to the attached jet theory, combining the theory modeling, field measurement and liquid scale model test. Based on the field measurement in a subway station in Shanghai, the field test data fit well with the theory calculation results in the initial segment of platform piston wind. The standard deviation between theory calculation and field measurement is between 0.326 and 0.542. The liquid scale model test is set up to verify the related mathematical model during the boundary layer district, potential flow core area and free shear zone in the initial segment. The model test results have good agreement with theory calculation with the standard deviation between 0.071 and 0.746. It is proved by above research works that the platform piston wind could be taken as the attached jet initial segment.